Adaptasi Mahasiswa Pendatang dalam Mencari Teman di Lingkungan Pendidikan Tinggi - Naufal Ashridyatama Mahendra; Oji Kurniadi (UNISBA Press, 2024)
Abstract. Intercultural communication involves various elements, such as language, social norms, and perception. The importance of understanding other people's cultures is to avoid miscommunication and conflict. This research focuses on understanding how culture influences the way we communicate and how effective communication can be established between immigrant students and the culture they receive. This research is supported by the theory of Anxiety Uncertainty Management by William B Gudykunst. This research explains how intercultural communication competence is used in the adaptations made by immigrant students to find friends in the Bandung Islamic University environment. This research uses a qualitative method with a case study approach. To obtain the data using interviews and observation. The results of this research look at the process of immigrant students in looking for friends in the campus environment, the inhibiting factors in finding friends, and the anxiety management carried out by immigrant students. In the process of finding friends, resource persons can adapt and open themselves to a new environment. In terms of inhibiting factors in finding friends, the interviewees had language barriers and different perceptions. In managing anxiety, the resource person is able to process their anxiety consciously. These efforts were made to determine the adaptation process of migrant students in finding friends in the Bandung Islamic University environment. Abstrak. Komunikasi antar budaya melibatkan berbagai elemen, seperti bahasa, norma sosial, dan persepsi. Pentingnya pemahaman terhadap budaya orang lain adalah untuk menghindari dari miskomunikasi dan konflik. Penelitian ini berfokus pada pemahaman tentang bagaimana budaya memengaruhi cara kita berkomunikasi dan bagaimana komunikasi yang efektif dapat dijalin antara mahasiswa pendatang dengan budaya yang mereka terima. Penelitian ini didukung oleh teori Anxiety Uncertainty Management oleh William B Gudykunst. Penelitian ini menjelaskan bagaimana kompetensi komunikasi antar budaya dalam adaptasi yang dilakukan mahasiswa pendatang untuk mencari teman di lingkungan Universitas Islam bandung. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Untuk memperoleh datanya menggunakan wawancara dan observasi. Hasil penelitian ini dilihat dari proses mahasiswa pendatang dalam mencari teman di lingkungan kampus, faktor penghambat dalam mencari teman, dan pengelolaan kecemasan yang dilakukan mahasiswa pendatang. Dalam tahap proses mencari teman narasumber bisa beradaptasi dan membuka diri di lingkungan yang baru. Dalam faktor penghambat dalam mencari teman, narasumber memiliki hambatan bahasa dan persepsi yang berbeda. Dalam pengelolaan kecemasan narasumber mampu mengolah kecemasan mereka secara sadar. Upaya-upaya tersebut dilakukan untuk mengetahui proses adaptasi mahasiswa pendatang dalam mencari teman di lingkungan Universitas Islam Bandung.